La yuxtaposición de sistemas en América Latina y sus consecuencias - Noejovich Chernoff, Héctor Omar (Pontificia Universidad Católica del Perú. Fondo Editorial, 2006)
This essay aim to set new hypothesis for Latin American’s development problem; the analysis is focused from “the encounter of two worlds” to the present. The generaland main hypothesis is a sort of “clutched” between the “Pre-Columbian System” and the “European System” and resulted in a so-called “Colonial System”. This “Colonial System” is defined as juxtaposition of systems and it has been suffering Western influence like a kind of “external shock” but keeping to an already hybrid system, wherein an inertial dynamic and not a dialectic one has been the main trait. The whole historical process is explained under such a point of view.

Este ensayo apunta a establecer nuevas hipótesis sobre el problema del desarrollo latinoamericano; el análisis está enfocado desde el encuentro de dos mundos hasta el presente. La principal y general hipótesis es el acoplamiento del sistema precolombino con el sistema europeo, que conformó el llamado sistema colonial. Este sistema colonial está definido como la yuxtaposición de sistemas, el mismo que ha recibido la influencia occidental como una suerte de shock externo, pero manteniendo un sistema híbrido en donde la dinámica inercial ha sido su rasgo principal y no una dinámica dialéctica. El complejo proceso histórico es explicado desde este punto de vista.
Keywords: Economía; Sistemas; América Latina; Yuxtaposición; Sociedad; Economía; Historia; https://purl.org/pe-repo/ocde/ford#5.02.01